2017
DOI: 10.1136/ejhpharm-2017-001255
|View full text |Cite
|
Sign up to set email alerts
|

Progression of systemic lupus erythematosus associated with propofol administration: a case report

Abstract: Propofol is a sedative-hypnotic agent used as a general anaesthetic with a good safety profile. However, the potential risk for patients with systemic lupuserythematosus (SLE) receiving propofol remains unclear. We report the case of a patient who received an intravenous infusion of propofol for painless gastroscopy which exacerbated acute SLE despite no history of allergies. The adverse effect might be because propofol increased T helper cells and trigged the induction of B cell differentiation and plasmablas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 17 publications
0
4
0
1
Order By: Relevance
“…The pathophysiology of this condition will also require more investigation, but the increase in helper T-cell activity in both SLE patients and routine propofol exposure is a potential basis for exploration. 3,10 Steroids anecdotally improved this patient's clinical course during multiple cutaneous reactions, but the best management proved to be removal of propofol from her anesthetic plan. A heightened awareness of this uncommon reaction to propofol may produce more documented cases, facilitate quicker diagnoses with better management, and, ideally, help to identify other high-risk patients for whom it may be best to avoid propofol and prevent PISCLE.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The pathophysiology of this condition will also require more investigation, but the increase in helper T-cell activity in both SLE patients and routine propofol exposure is a potential basis for exploration. 3,10 Steroids anecdotally improved this patient's clinical course during multiple cutaneous reactions, but the best management proved to be removal of propofol from her anesthetic plan. A heightened awareness of this uncommon reaction to propofol may produce more documented cases, facilitate quicker diagnoses with better management, and, ideally, help to identify other high-risk patients for whom it may be best to avoid propofol and prevent PISCLE.…”
Section: Discussionmentioning
confidence: 99%
“…2 Diligent review of the anesthetic records of this patient suggested propofol was likely associated with the patient’s postoperative rashes, a potential side effect of propofol that is infrequently described. 3 By removing propofol from the anesthetic plans of both her DIEP flap and reconstruction revision, and observing no perioperative cutaneous changes for the first time in her lengthy surgical history, the case was strengthened that propofol had very likely been responsible for her 7 previous eruptions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recientemente, se ha reportado un caso de exacerbación de LES gatillada por propofol. Se ha visto que éste puede aumentar la actividad de linfocitos T helper y la diferenciación de linfocitos B, aumentando la producción de anticuerpos, especialmente en pacientes con anticuerpos anti-DNA y antinucleares positivos, aunque faltan estudios para demostrar la significancia clínica de esto [17].…”
Section: Farmacoterapia Efectos Adversos E Interacciones Farmacológic...unclassified